2020
DOI: 10.3389/fphy.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Swimming of Motile Gyrotactic Microorganisms and Nanoparticles in Blood Flow Through Anisotropically Tapered Arteries

Abstract: In the present article, we have presented a theoretical study on the swimming of migratory gyrotactic microorganisms in a non-Newtonian blood-based nanofluid via an anisotropically narrowing artery. Sutterby fluid model is used in order to understand the rheology of the blood as a non-Newtonian fluid model. This fluid pattern has the ability to show Newtonian and non-Newtonian features. The mathematical formulation is performed via continuity, temperature, motile microorganism, momentum, and concentration equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…Ali et al [ 17 ] investigated the hybrid TiO and Cu-H O nanofluid under slip and magnetic forces via the peristaltic mechanism. Some recent studies associated with the current topic can be found from the references [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [ 17 ] investigated the hybrid TiO and Cu-H O nanofluid under slip and magnetic forces via the peristaltic mechanism. Some recent studies associated with the current topic can be found from the references [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are no experimental results dealing with the blood as a two-phase model (plasma and red blood cells) in stenosis artery. Studying the blood flow through a stenosis was the objective of many authors as [2] and [4][5][6][7][8][9][10][11][12][13] attempting to understand the harmful effect on the human. Also, a review article [14] gives more attention on the flow through stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Works in the field have highlighted the main aspects that appeared in such studies [19,20]. Some similar results can be found in [21][22][23]. The theoretical approach of the properties of the symmetry group allows obtaining valuable and useful information from a practical point of view about the mechanical response or the properties of such a system, before performing any real calculations.…”
Section: Introductionmentioning
confidence: 67%